Design and Evaluation of an AI-Driven Gamified Intelligent Tutoring System for Fundamental Programming Using the Octalysis Framework - Dzaky Fatur Rahman; Fenina Adline Twince Tobing; Cian Ramadhona Hassolthine (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2025)
This research aims to address the challenges of student motivation and engagement in fundamental programming education by implementing the Octalysis Gamification Framework within an Intelligent Learning System. Traditional learning methods often fail to visualize abstract concepts or provide personalized feedback, leading to student demotivation. To overcome this, a platform named